Financial ecological environment and internal audit outsourcing: Evidence from survey in China - Jing Du; Wanfu Li; Bin Lin; Donghui Wu (China Journal of Accounting Studies (CJAS), 2021)
This paper examines the determinants of internal audit outsourcing from the macro perspective of financial ecological environment. We find that in regions with a poor financial ecological environment, firms are more likely to outsource internal audit and more inclined to outsource to other service providers than to accounting firms that provide financial report audit services for them. Furthermore, those firms with high financing constraints and non-state-owned firms are more likely to outsource internal audit in poor financial ecological environments. Firms outsourcing internal audit in poor financial ecological environments will have low debt financing costs. These results suggest firms in weak financial ecological environments tend to use internal audit outsourcing to enhance investor confidence and reduce financing costs. This paper helps expand the literature related to the determinants of internal audit outsourcing from a macro perspective, and provide a reference for improving the resource-allocation efficiency of the governance-oriented internal audit.
Keywords: 650; Financial ecological environment; internal audit outsourcing; external audit; financing costs